Different behavior of two iso‐structural zeolitic imidazolate frameworks in ethane–ethylene separation: Study of H2‐CO2 and CH4‐CO2 separation capacity. Issue 17 (12th August 2021) - Autié‐Castro, Giselle; Reguera, Edilso; Rodríguez‐Castellón, Enrique
Abstract: The separation of ethane–ethylene mixtures was evaluated using two zeolitic imidazolate frameworks, which are only different from the assemble metal, as stationary phase from inverse gas chromatography data. The chromatographic profiles exhibited peaks adequately resolved. Separation is attributed to the pore sizes of the adsorbents that discern between ethane and ethylene molecule shapes and closed kinetic diameters. The adsorption heats were estimated for each probe molecule from the slopes of the straight lines at four temperatures. The evaluated materials are iso‐structural compounds with the unique difference of assembling metal (cobalt and zinc). Cobalt material showed atypical adsorption of ethane over ethylene, which was observed taking into account the retarded elution of the paraffin. Therefore, the anomalous behavior could be ascribed to the presence of cobalt(II). Structural characterization of both materials was performed by X‐ray powder diffraction, X‐ray photoelectronic spectroscopy, and thermogravimetry, while morphological characterization was performed by scanning electron microscopy. H2 ‐CO2 and CH4 ‐CO2 mixtures separation were also evaluated by inverse gas chromatography. Both materials were able to separate these two mixtures. CO2 was the highest retained probe molecule due to the presence of quadrupole moment.